Developing Linguistic Strategies to Boost Engagement and Branding of Micro-Influencers in Indonesia - Linda, Linda; Rozak, Diana Rahmawati (IJELR: International Journal of Education, Language, and Religion, 2025)
The phenomenon of micro-influencers in Indonesia continues to grow alongside the increasing use of social media in digital marketing. One of the key factors determining the success of micro-influencers in building engagement and branding is the linguistic strategies they employ. However, in-depth studies on how language use can enhance audience interaction and brand appeal remain limited. Therefore, this study aims to develop an effective model of linguistic strategies for micro-influencers to boost audience engagement and strengthen their personal branding.This research adopts a qualitative method with digital discourse analysis of micro-influencer content on platforms such as Instagram, TikTok, and YouTube. Data were collected through sampling of social media posts, interviews with micro-influencers and their audiences, and analysis of interactions in the form of comments and engagement metrics. The analytical techniques used include critical discourse analysis to identify communication patterns, sentiment analysis to measure audience responses, and the development of a conceptual model of linguistic strategies based on the findings. The results of this study not only contribute academically to the field of digital linguistics but also have practical implications in helping micro-influencers and brands optimize their communication strategies on social media.